Positive active material for lithium secondary battery, method for preparing the same, and lithium secondary battery comprising the same

CN116325224BActive Publication Date: 2026-10-23ECOPRO BM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180067086.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-21
Filing Date
2021-12-02
Publication Date
2026-10-23
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

[0006]本发明的目的在于,通过抑制二次电池用正极活性物质寿命循环中的相变来增加充放电容量并解决寿命劣化及电压衰减的问题

Benefits of technology

[0017]本发明实施例的二次电池用正极活性物质通过抑制二次电池用正极活性物质寿命循环中的相变来增加充放电容量并解决寿命劣化及电压衰减的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116325224B_ABST
    Figure CN116325224B_ABST
Patent Text Reader

Abstract

The positive electrode active material for a secondary battery according to an embodiment of the present application contains a lithium complex oxide, the lithium complex oxide contains a lithium-excess oxide having a layered structure represented by the following Chemical Formula 1, the lithium complex oxide contains secondary particles, the secondary particles contain one or more primary particles, the primary particles contain one or more crystal grains, one or more selected from the secondary particles, the primary particles, and the crystal grains contain a core and a shell occupying at least a part of a surface of the core, and when a molar number of one or more elements selected from nickel (Ni), cobalt (Co), and manganese (Mn) with respect to a total molar number of M1 and M2 of the following Chemical Formula 1 is NCM / M, the NCM / M of the shell and the core of the secondary particles are different.[Chemical Formula 1] rLi2M1O3·(1-r)Li a M2O2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a positive electrode active material for secondary batteries comprising a lithium composite oxide containing a layered structure of lithium excess oxide. Background Technology

[0002] With the development of portable mobile electronic devices such as smartphones, MP3 players, and tablets, the demand for rechargeable batteries capable of storing electrical energy has exploded. In particular, the emergence of electric vehicles, medium and large-scale energy storage systems, and portable devices requiring high energy density has further increased the demand for lithium-ion rechargeable batteries.

[0003] The most recently discussed positive electrode active material is lithium nickel manganese cobalt oxide (Li(Ni)) x Co y Mn z O2 (where x, y, and z are the atomic fractions of the constituent elements of each independent oxide, 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, 0 < x + y + z ≤ 1). Compared with the previously actively researched and used positive electrode active material LiCoO2, this material has the advantage of high capacity due to its use at high voltage, and its relatively low Co content makes it inexpensive. However, it has the disadvantages of poor rate capability and poor lifespan characteristics at high temperatures.

[0004] Therefore, a process was carried out that will surpass the existing Li(Ni) x Co y Mn z The application of lithium-excess layered oxides with high reversible capacity exhibited by O2 in the research of lithium secondary batteries.

[0005] However, the reduction in discharge capacity and voltage decay during the cycle life becomes a problem, caused by the transition metal's phase transformation into a spinel-like structure. These issues must be addressed for the commercialization of lithium-ion batteries. Summary of the Invention

[0006] The purpose of this invention is to increase charge and discharge capacity and solve the problems of lifespan degradation and voltage decay by suppressing phase transitions in the positive electrode active material of secondary batteries during lifetime cycling.

[0007] Furthermore, the purpose of this invention is to increase the lithium-ion mobility and improve the rate performance of the positive electrode active material for secondary batteries.

[0008] Furthermore, the purpose of this invention is to improve the surface kinetics and structural stability of the positive electrode active material for secondary batteries.

[0009] Technical solution

[0010] To address the aforementioned problems, the positive electrode active material for secondary batteries in this embodiment of the invention comprises a lithium composite oxide, wherein the lithium composite oxide comprises an excess lithium oxide with a layered structure represented by the following chemical formula 1, the lithium composite oxide comprises secondary particles, the secondary particles comprise one or more primary particles, the primary particles comprise one or more grains, and one or more selected from the secondary particles, primary particles, and grains comprises a core and a shell occupying at least a portion of the surface of the core. When the molar number of one or more elements selected from nickel (Ni), cobalt (Co), and manganese (Mn) is NCM / M relative to the total molar number of M1 and M2 of the following chemical formula 1, the NCM / M of the shell and the core of the secondary particles are different.

[0011] Chemical formula 1: rLi₂M₁O₃·(1-r)Li a M2O2

[0012] In the above chemical formula 1, 0 < r < 1, 0 < a ≤ 1, M1 contains one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi, and M2 contains one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi.

[0013] Furthermore, as a more preferred example, the shell of the aforementioned secondary particles may include a concentration gradient section in which the concentrations of one or more elements selected from nickel, cobalt, and manganese are gradient.

[0014] Furthermore, as a more preferred example, the shell of the primary particle may include a concentration gradient section in which the concentrations of one or more elements selected from nickel, cobalt, and manganese are gradient.

[0015] Furthermore, as a more preferred example, the shell of the aforementioned grain may include a concentration gradient portion in which the concentrations of one or more elements selected from nickel (Ni), cobalt (Co), and manganese (Mn) are gradient.

[0016] The effects of the invention

[0017] The positive electrode active material for secondary batteries in this embodiment of the invention increases charge and discharge capacity and solves the problems of lifespan degradation and voltage decay by suppressing phase transitions during the life cycle of the positive electrode active material for secondary batteries.

[0018] Furthermore, the positive electrode active material for secondary batteries in this embodiment of the invention increases lithium-ion mobility and improves rate performance.

[0019] Furthermore, the positive electrode active material for secondary batteries in this embodiment of the invention improves surface motion and structural stability. Attached Figure Description

[0020] Figure 1 The FQ-EDS analysis results are for the comparative and exemplary examples.

[0021] Figure 2 The FQ-EDS analysis results are for the positive electrode active materials of the comparative examples and embodiments.

[0022] Figure 3 The FQ-EDS analysis results are for the positive electrode active materials of the comparative examples and embodiments.

[0023] Figure 4 The results are from the transmission electron microscopy-dispersive spectroscopy (TEM-EDS) analysis of Example 1.

[0024] Figure 5 The results are from the transmission electron microscopy-dispersive spectroscopy analysis of Example 1.

[0025] Figure 6 The results are from transmission electron microscopy-dispersive spectroscopy and concentration gradient analysis of Example 1.

[0026] Figure 7 The results are from transmission electron microscopy-dispersive spectroscopy and concentration gradient analysis of Example 1.

[0027] Figure 8 The results are from transmission electron microscopy-dispersive spectroscopy and concentration gradient analysis in Example 5.

[0028] Figure 9 The results of scanning electron microscopy (SEM) analysis are shown for comparative and exemplary cases.

[0029] Figure 10 The initial voltage curve analysis results are for the comparative examples and embodiments.

[0030] Figure 11 The results of the rate performance analysis are for the comparative examples and embodiments.

[0031] Figure 12 The results of the rate performance analysis are for the comparative examples and embodiments.

[0032] Figure 13 The lifetime characteristics analysis results are for comparative examples and embodiments.

[0033] Figure 14The lifetime characteristics analysis results are for comparative examples and embodiments.

[0034] Figure 15 The voltage characteristic analysis results are for the comparative examples and embodiments.

[0035] Figure 16 The voltage characteristic analysis results are for the comparative examples and embodiments. Detailed Implementation

[0036] The terms “comprising” and similar expressions used in this specification should be understood as open-ended terms that imply the possibility of including other technical features.

[0037] As used in this specification, "as an example," "as an embodiment," and "preferred" refer to embodiments of the invention that provide the specified advantages under the specified conditions, and are not intended to exclude other embodiments from the scope of the invention.

[0038] The positive electrode active material for secondary batteries in this embodiment of the invention comprises a lithium composite oxide containing a lithium excess oxide with a layered structure represented by the following chemical formula 1.

[0039] Chemical formula 1: rLi₂M₁O₃·(1-r)Li a M2O2

[0040] In the above chemical formula 1, 0 < r < 1, 0 < a ≤ 1, M1 and M2 are independent of each other, M1 is selected from one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi, and M2 is selected from one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi.

[0041] As a more preferred example, M1 is selected from one or more of Mn, Cr, Fe, Co, Ni, Mo, Ru, W, Ti, Zr, Sn, V, Al, Mg, Ta, B, P, Nb, Cu, La, Ba, Sr, and Ce, and M2 is selected from one or more of Ni, Co, Mn, Cr, Fe, Mo, Ru, W, Ti, Zr, Sn, V, Al, Mg, Ta, B, P, Nb, Cu, La, Ba, Sr, and Ce.

[0042] As an example, in the above chemical formula 1, the aforementioned lithium excess oxide can be Li₂M₁O₃ with a monoclinic structure and Li₂ with a rhombohedral structure. a The solid solution phase in which M2O2 is mixed.

[0043] As a more preferred example, the average valence of M1 can be 3.5 to 4.5, or 4.

[0044] As a more preferred example, the average valence of M2 can be 2.5 to 3.5, or it can be 3.

[0045] Furthermore, as a more preferred example, the above chemical formula 1 can be as shown in the following chemical formula 1-1.

[0046] Chemical formula 1-1: rLi2Mn p Md1 1-p O3·(1-r)Li a Ni x Co y Mn z Md2 1-(x+y+z) O2

[0047] In the above chemical formula 1, 0 < r < 1, 0 < p ≤ 1, 0 < a ≤ 1, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < x + y + z ≤ 1, Md1 and Md2 are independent of each other, Md1 is selected from one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi, and Md2 is selected from one or more of Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi.

[0048] The aforementioned Md1 and Md2 can each be independently elements constituting the crystal lattice, dopants, or coating materials, and the target effect of the present invention can be obtained regardless of the types of Md1 and Md2.

[0049] As a more preferred example, Md1 is selected from one or more of Cr, Fe, Co, Ni, Mo, Ru, W, Ti, Zr, Sn, V, Al, Mg, Ta, B, P, Nb, Cu, La, Ba, Sr and Ce, and Md2 is selected from one or more of Cr, Fe, Mo, Ru, W, Ti, Zr, Sn, V, Al, Mg, Ta, B, P, Nb, Cu, La, Ba, Sr and Ce.

[0050] As an example, in the above chemical formula 1-1, the above-mentioned lithium excess oxide can be Li₂Mn with a monoclinic crystal structure. p Md1 1-p O3 and Li with rhombohedral structure a Ni x Co y Mn z Md 1-(x+y+z) A solid solution phase containing O2.

[0051] As an example, the aforementioned lithium excess oxide can be a layered structure in which lithium atomic layers are alternately stacked with nickel, cobalt, manganese or Md atomic layers through oxygen atomic layers.

[0052] As an example, the above r value can be below 1, below 0.9, below 0.8, below 0.7, or below 0.6.

[0053] As an example, the above p can be greater than 0, and can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or above, or 1.0.

[0054] As a more preferred example, the Li / M ratio of the number of moles of lithium in the lithium composite oxide of the present invention relative to the total number of moles of M1 and M2 can be 1.01 or more, 1.05 or more, 1.1 or more, or 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, or 1.3 or less.

[0055] As a more preferred example, the Ni / M ratio of the above-mentioned lithium composite oxide relative to the total number of moles of M1 and M2 can be 0.1, 0.2 or 0.3 or more, or 0.7 or less, 0.6 or less or 0.5 or less.

[0056] As a more preferred example, the Co / M ratio of the cobalt molar number of the lithium composite oxide relative to the total molar number of M1 and M2 can be 0.0, 0.05 or more, or 0.3, 0.2 or less.

[0057] As a more preferred example, the positive electrode active material of one embodiment of the present invention may not contain Co.

[0058] As a more preferred example, the ratio Mn / M of the number of manganese moles in the lithium composite oxide relative to the total number of moles of M1 and M2 can be 0.1, 0.2, or 0.3 or more, or 0.8 or 0.7 or less.

[0059] As a more preferred example, the Md2 / M ratio of the number of moles of Md2 in the above-mentioned lithium composite oxide relative to the total number of moles of M1 and M2 can be 0.0 or more, or 0.2 or less than 0.1.

[0060] Furthermore, the aforementioned lithium composite oxide contains secondary particles, each of which contains one or more primary particles, and each primary particle contains one or more crystallites.

[0061] In the description of this invention, "one or more" means one or two or more.

[0062] As an example, the aforementioned secondary particle may contain one primary particle, or it may be formed by the aggregation of two or more primary particles.

[0063] As an example, the aforementioned primary particles can contain one grain, or can be formed by the aggregation of two or more grains.

[0064] Furthermore, a shell consisting of a core and a surface occupying at least a portion of the surface of the aforementioned secondary particles, primary particles, and grains.

[0065] As an example, the aforementioned secondary particle can be a particle with a core-shell structure that includes a nucleus and a shell occupying at least a portion of the surface of the nucleus.

[0066] In this case, "at least a portion" can mean that the total surface area of ​​the secondary particles is greater than 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%.

[0067] The average particle size (D50) of the aforementioned secondary particles can range from 0.5 μm to 20 μm.

[0068] As an example, the thickness of the shell of the aforementioned secondary particles can be greater than 0 μm and less than or equal to 10 μm, greater than 0 μm and less than or equal to 1 μm, greater than 0 nm and less than or equal to 500 nm, greater than 0 nm and less than or equal to 400 nm, greater than 0 nm and less than or equal to 300 nm, greater than 0 nm and less than or equal to 200 nm, greater than 0 nm and less than or equal to 150 nm, greater than 0 nm and less than or equal to 100 nm, greater than 0 nm and less than or equal to 90 nm, greater than 0 nm and less than or equal to 80 nm, greater than 0 nm and less than or equal to 70 nm, greater than 0 nm and less than or equal to 60 nm, or greater than 0 nm and less than or equal to 50 nm.

[0069] As an example, the thickness of the shell of the aforementioned secondary particle can be greater than 0.0%, 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% of the length of the secondary particle, or less than 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, or 1%.

[0070] As an example, the aforementioned primary particle may include a nucleus and a shell occupying at least a portion of the surface of the nucleus.

[0071] In this case, "at least a portion" can mean that the total surface area of ​​the primary particles is greater than 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%.

[0072] As an example, the thickness of the shell of the aforementioned primary particle can be greater than 0 μm and less than or equal to 10 μm, greater than 0 μm and less than or equal to 1 μm, greater than 0 nm and less than or equal to 500 nm, greater than 0 nm and less than or equal to 400 nm, greater than 0 nm and less than or equal to 300 nm, greater than 0 nm and less than or equal to 200 nm, greater than 0 nm and less than or equal to 150 nm, greater than 0 nm and less than or equal to 100 nm, greater than 0 nm and less than or equal to 90 nm, greater than 0 nm and less than or equal to 80 nm, greater than 0 nm and less than or equal to 70 nm, greater than 0 nm and less than or equal to 60 nm, or greater than 0 nm and less than or equal to 50 nm.

[0073] As an example, the thickness of the shell of the primary particle can be greater than 0.0%, 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% of the length of the primary particle, or less than 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, or 1%.

[0074] As an example, the aforementioned grain may include a core and a shell occupying at least a portion of the surface of the core.

[0075] In this case, "at least a portion" can mean that the total surface area of ​​the primary grains is greater than 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%.

[0076] As an example, the thickness of the shell of the aforementioned grain can be greater than 0 μm and less than or equal to 10 μm, greater than 0 μm and less than or equal to 1 μm, greater than 0 nm and less than or equal to 500 nm, greater than 0 nm and less than or equal to 400 nm, greater than 0 nm and less than or equal to 300 nm, greater than 0 nm and less than or equal to 200 nm, greater than 0 nm and less than or equal to 150 nm, greater than 0 nm and less than or equal to 100 nm, greater than 0 nm and less than or equal to 90 nm, greater than 0 nm and less than or equal to 80 nm, greater than 0 nm and less than or equal to 70 nm, greater than 0 nm and less than or equal to 60 nm, or greater than 0 nm and less than or equal to 50 nm.

[0077] As an example, the thickness of the shell of the aforementioned grain can be greater than 0.0%, 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% of the grain length, or less than 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, or 1%.

[0078] In this context, the "core" of a secondary particle, primary particle, or grain refers to the region near the center of the particle, excluding the particle's surface, located inside the secondary particle, primary particle, or grain. Furthermore, the "shell" refers to the region near the surface of the particle, excluding the particle's center or interior.

[0079] The "core" and "shell" of the secondary particles, primary particles, or grains of the present invention can be distinguished by a point centered on the mole fraction of the contained elements or a point distinguishing the pattern of concentration change. For example, this could refer to a point in the shell of a secondary particle, primary particle, or grain where the concentration of Ni decreases sharply from the surface to the center, and the gradient in the core slows down, remains at a predetermined level, or increases. Similarly, this could refer to a point in the shell of a secondary particle, primary particle, or grain where the concentration of Co decreases sharply from the surface to the center, and the gradient in the core slows down, remains at a predetermined level, or increases. Likewise, this could refer to a point in the shell of a secondary particle, primary particle, or grain where the concentration of Mn decreases sharply from the surface to the center, and the gradient in the core slows down, remains at a predetermined level, or increases.

[0080] In one embodiment of the present invention, the positive electrode active material can form a shell distinct from the core by diffusing transition metals such as nickel, cobalt, and / or manganese into secondary particles, primary particles, and / or grains.

[0081] Furthermore, in one embodiment of the present invention, when the molar number of one or more elements selected from nickel, cobalt and manganese is NCM / M relative to the total molar number of M1 and M2, the NCM / M of the shell and the core of the aforementioned secondary particles are different.

[0082] This indicates that, when the interior of the aforementioned secondary particle is cross-sectioned to confirm its cross-section, the NCM / M of the shell and the nucleus of the aforementioned secondary particle are different.

[0083] As an example, when the number of moles of nickel relative to the total number of moles of M1 and M2 is Ni / M, the Ni / M of the shell and the core of the aforementioned secondary particles can be different.

[0084] As an example, when the number of moles of cobalt relative to the total number of moles of M1 and M2 is Co / M, the Co / M of the shell and the core of the aforementioned secondary particles can be different.

[0085] As an example, when the number of moles of cobalt relative to the total number of moles of M1 and M2 is Mn / M, the Mn / M of the shell and the core of the aforementioned secondary particles can be different.

[0086] As a more preferred example, the shell of the secondary particle may include a concentration gradient section in which the concentrations of one or more elements selected from nickel, cobalt and manganese are gradient.

[0087] This can mean that, when the interior of the aforementioned secondary particle is cross-sectioned to confirm its cross-section, the shell of the aforementioned secondary particle contains a concentration gradient portion in which the concentration of one or more elements selected from nickel, cobalt, and manganese has a gradient.

[0088] Furthermore, in one embodiment of the present invention, the NCM / M ratio of the shell and core of the primary particles of the positive electrode active material may be different.

[0089] This could mean that, when the interior of the aforementioned primary particle is cross-sectioned to confirm its cross-section, the NCM / M of the shell and nucleus of the aforementioned primary particle are different.

[0090] As an example, the Ni / M ratio of the shell and the core of the aforementioned primary particle can be different.

[0091] As an example, the Co / M ratio of the shell and the nucleus of the aforementioned primary particle can be different.

[0092] As an example, the Mn / M ratio of the shell and the nucleus of the aforementioned primary particle can be different.

[0093] The aforementioned primary particles can be primary particles that are in contact with the surface of secondary particles, or they can include primary particles that exist in the nucleus of secondary particles.

[0094] As a more preferred example, the shell of the primary particle may include a concentration gradient section in which the concentrations of one or more elements selected from nickel, cobalt and manganese are gradient.

[0095] This can mean that, when the interior of the aforementioned primary particle is cross-sectioned to confirm its cross-section, the shell of the aforementioned primary particle contains a concentration gradient portion in which the concentration of one or more elements selected from nickel, cobalt, and manganese has a gradient.

[0096] Furthermore, in one embodiment of the present invention, the NCM / M ratio of the shell and core of the above-mentioned positive electrode active material may be different.

[0097] This indicates that, when the interior of the aforementioned grain is cross-sectioned to confirm its cross-section, the NCM / M of the shell and core of the aforementioned grain are different.

[0098] As an example, the Ni / M ratio of the shell and the core of the above-mentioned grains can be different.

[0099] As an example, the Co / M ratio of the shell and the core of the above-mentioned grains can be different.

[0100] As an example, the Mn / M ratio of the shell and core of the above-mentioned grains can be different.

[0101] As a more preferred example, the shell of the aforementioned grain may include a concentration gradient portion in which the concentrations of one or more elements selected from nickel, cobalt, and manganese are gradient.

[0102] This can mean that, when the interior of the grain is cross-sectioned to confirm its cross-section, the shell of the grain contains a concentration gradient portion in which the concentration of one or more elements selected from nickel, cobalt, and manganese has a gradient.

[0103] As a more preferred example of the present invention, not only secondary particles and primary particles, but also the shell of the grain can form a concentration gradient of transition metal.

[0104] As a more preferred example, the Ni / M ratio of the shell selected from one or more of the above-mentioned secondary particles, primary particles and grains can be higher than that of the above-mentioned core.

[0105] As a more preferred example, the shell of the secondary particle may include a concentration gradient portion in which the concentration of nickel decreases from the surface of the secondary particle toward the center.

[0106] As a more preferred example, the shell of the primary particle may include a concentration gradient portion in which the concentration of nickel decreases from the surface of the primary particle toward the center.

[0107] As a more preferred example, the shell of the aforementioned grain may include a concentration gradient portion in which the concentration of nickel decreases from the surface of the grain toward the center.

[0108] As a more preferred example, the Co / M ratio of the shell selected from the above-mentioned secondary particles, primary particles and grains can be higher than that of the above-mentioned core.

[0109] As a more preferred example, the shell of the secondary particle may include a concentration gradient portion in which the concentration of cobalt decreases from the surface of the secondary particle toward the center.

[0110] As a more preferred example, the shell of the primary particle may include a concentration gradient portion in which the concentration of cobalt decreases from the surface of the primary particle toward the center.

[0111] As a more preferred example, the shell of the aforementioned grain may include a concentration gradient portion in which the cobalt concentration decreases from the surface of the grain toward the center.

[0112] As another preferred example, the positive electrode active material of one embodiment of the present invention may not contain cobalt.

[0113] In this case, even without using expensive cobalt, a concentration gradient of nickel or manganese can be included in the shell of secondary particles, primary particles, or grains to suppress phase transitions during the life cycle of the positive electrode active material for secondary batteries, increase charge and discharge capacity, and thus solve the problems of life degradation and voltage decay.

[0114] As a more preferred example, the Mn / M ratio of the shell, which is selected from one or more of the secondary particles, primary particles and grains mentioned above, can be lower than that of the core.

[0115] As a more preferred example, the shell of the secondary particle may include a concentration gradient portion in which the concentration of manganese increases from the surface of the secondary particle toward the center.

[0116] As a more preferred example, the shell of the primary particle may include a concentration gradient portion in which the concentration of manganese increases from the surface of the primary particle toward the center.

[0117] As a more preferred example, the shell of the aforementioned grain may include a concentration gradient portion in which the concentration of manganese increases from the surface of the grain toward the center.

[0118] Furthermore, as a more preferred example of the present invention, the gradient of nickel concentration gradient can be maximized in the shells of secondary particles, primary particles, and / or grains compared to manganese or cobalt.

[0119] Furthermore, as a more preferred example, the concentration gradient of manganese can be maximized in the shells of secondary particles, primary particles, and / or grains compared to nickel or cobalt.

[0120] Furthermore, as a more preferred example, the concentration gradient of cobalt can be maximized in the shells of secondary particles, primary particles, and / or grains compared to nickel or manganese.

[0121] Furthermore, as a more preferred example of the present invention, the maximum value of Ni / M in the shell of the aforementioned secondary particles, primary particles, and / or grains can be greater than the minimum value of Mn / M.

[0122] Furthermore, as a more preferred example, in the shell of the aforementioned secondary particles, primary particles, and / or grains, the maximum value of Co / M can be smaller than the minimum value of Mn / M.

[0123] Furthermore, as a more preferred example, the nuclei of the aforementioned secondary particles, primary particles, and / or grains can be Mn / M > Ni / M > Co / M.

[0124] Furthermore, as a more preferred example, in the nuclei of the aforementioned secondary particles, primary particles, and / or grains, Ni / M can be 0.1, 0.2, or 0.3 or more, or 1.0, 0.9, or 0.8 or less.

[0125] Furthermore, as a more preferred example, in the nuclei of the aforementioned secondary particles, primary particles, and / or grains, Co / M can be 0.3, 0.2, 0.1, or 0.05 or less, or 0.0 or more.

[0126] Furthermore, as a more preferred example, in the nuclei of the aforementioned secondary particles, primary particles, and / or grains, Mn / M can be 0.4, 0.5, or 0.6 or more, or 1.0, 0.9, or 0.8 or less.

[0127] Furthermore, as a more preferred example of the present invention, in the shell of the aforementioned secondary particles, primary particles, and / or grains, the maximum value of Ni / M can be 5 mole percentage, 10 mole percentage, 15 mole percentage, 20 mole percentage, 25 mole percentage, 30 mole percentage, 35 mole percentage, 40 mole percentage, 45 mole percentage, 50 mole percentage, 55 mole percentage, 60 mole percentage, 65 mole percentage, 70 mole percentage, 75 mole percentage, 80 mole percentage, 85 mole percentage, 90 mole percentage, or 95 mole percentage or more, or can be 100 mole percentage, 95 mole percentage, 90 mole percentage, 85 mole percentage, 80 mole percentage, 75 mole percentage, 70 mole percentage, 65 mole percentage, 60 mole percentage, 55 mole percentage, 50 mole percentage, 45 mole percentage, 40 mole percentage, 35 mole percentage, 30 mole percentage, 25 mole percentage, 20 mole percentage, 15 mole percentage, or less than 10 mole percentage.

[0128] Furthermore, as a more preferred example, in the shell of the aforementioned secondary particles, primary particles, and / or grains, the maximum value of Co / M can be 1 mole percentage, 3 mole percentage, 5 mole percentage, 10 mole percentage, 15 mole percentage, 20 mole percentage, 25 mole percentage, 30 mole percentage, 35 mole percentage, 40 mole percentage, 45 mole percentage, 50 mole percentage, 55 mole percentage, 60 mole percentage, 65 mole percentage, 70 mole percentage, 75 mole percentage, 80 mole percentage, 85 mole percentage, 90 mole percentage, or more than 95 mole percentage, and can be 100 mole percentage, 95 mole percentage, 90 mole percentage, 85 mole percentage, 80 mole percentage, 75 mole percentage, 70 mole percentage, 65 mole percentage, 60 mole percentage, 55 mole percentage, 50 mole percentage, 45 mole percentage, 40 mole percentage, 35 mole percentage, 30 mole percentage, 25 mole percentage, 20 mole percentage, 15 mole percentage, or less than 10 mole percentage.

[0129] Furthermore, as a more preferred example, in the shell of the aforementioned secondary particles, primary particles, and / or grains, the minimum value of Mn / M can be 5 mole percentage, 10 mole percentage, 15 mole percentage, 20 mole percentage, 25 mole percentage, 30 mole percentage, 35 mole percentage, 40 mole percentage, 45 mole percentage, 50 mole percentage, 55 mole percentage, 60 mole percentage, 65 mole percentage, 70 mole percentage, 75 mole percentage, 80 mole percentage, 85 mole percentage, 90 mole percentage, or more than 95 mole percentage, and can be 100 mole percentage, 95 mole percentage, 90 mole percentage, 85 mole percentage, 80 mole percentage, 75 mole percentage, 70 mole percentage, 65 mole percentage, 60 mole percentage, 55 mole percentage, 50 mole percentage, 45 mole percentage, 40 mole percentage, 35 mole percentage, 30 mole percentage, 25 mole percentage, 20 mole percentage, 15 mole percentage, or less than 10 mole percentage.

[0130] Furthermore, as an example, the ratio of the R-3m space group to the C2 / m space group in the core and shell of the aforementioned secondary particles, primary particles, and / or grains can be different.

[0131] Furthermore, as an example, the Ni in the core and shell of the aforementioned secondary particles, primary particles, and / or grains... 3+ and Ni 2+ The proportions can be different.

[0132] Furthermore, as an example, the Mn in the core and shell of the aforementioned secondary particles, primary particles, and / or grains 3+ and Mn4+ The proportions can be different.

[0133] The positive electrode active material in embodiments of the present invention may further comprise an additional coating. The coating may comprise one or more coating materials selected from P, Nb, Si, Sn, Al, Pr, Al, Ti, Zr, Fe, Al, Fe, Co, Ca, Mn, Ti, Sm, Zr, Fe, La, Ce, Pr, Mg, Bi, Li, W, Co, Zr, B, Ba, F, K, Na, V, Ge, Ga, As, Sr, Y, Ta, Cr, Mo, W, Mn, Ir, Ni, Zn, In, Na, K, Rb, Cs, Fr, Sc, Cu, Ru, Rh, Pd, Ag, Cd, Sb, Hf, Ta, Re, Os, Pt, Au, Pb, Bi, and Po, but is not limited thereto.

[0134] The coating can improve lifespan and increase fill density by blocking the contact between the positive electrode active material and the electrolyte contained in the lithium secondary battery, thus inhibiting the occurrence of side reactions. It can also act as a lithium-ion conductor.

[0135] Furthermore, the coating can be formed on the entire surface of the positive electrode active material or on the entire surface of the primary particles, or it can be formed partially. Moreover, the coating can be a single-layer coating, a double-layer coating, a particle-based coating, a uniform coating, or an Irish coating.

[0136] The positive electrode active material in this invention can form a lithium-ion diffusion pathway inside primary particles.

[0137] In the positive electrode active material of the present invention, the surface of the layer forming the above-mentioned layered structure can have crystal orientation in the primary particle along the direction perpendicular to the C-axis, and can form a lithium ion movement pathway in the center direction of the positive electrode active material particle inside or outside the primary particle.

[0138] The following describes a method for preparing a positive electrode active material for a secondary battery according to an embodiment of the present invention.

[0139] First, the process of forming precursor particles is carried out.

[0140] As a more preferred example, the aforementioned precursor particles can be prepared by co-precipitation, or by adding a complexing agent.

[0141] Next, the precursor particles formed above are subjected to a first heat treatment at a temperature of 300°C to 1000°C and then cooled.

[0142] Next, after the cooling step following the first heat treatment described above, a wet coating step can be performed with a compound containing one or more elements selected from cobalt, nickel, and manganese.

[0143] Next, the particles cooled after the first heat treatment or the particles of the wet coating are mixed with the first lithium compound and then cooled after the second heat treatment at a temperature of 800°C to 1000°C.

[0144] Next, after the cooling step following the second heat treatment described above, a wet coating step can be performed with a compound containing one or more elements selected from cobalt, nickel, and manganese.

[0145] Next, the particles cooled after the second heat treatment or the particles of the wet coating are mixed with the second lithium compound and then cooled after the third heat treatment at a temperature of 300°C to 1000°C.

[0146] An embodiment of the present invention may include a wet coating step with a compound containing one or more elements selected from cobalt, nickel and manganese, which may be performed after the step of forming precursor particles and before the step of first heat treatment followed by cooling, between the step of first heat treatment followed by cooling and the step of second heat treatment followed by cooling, or between the step of second heat treatment followed by cooling and the step of third heat treatment followed by cooling.

[0147] As a more preferred example, the above-mentioned wet coating step can be prepared by co-precipitation, which can be done by adding a complexing agent.

[0148] The secondary battery of this invention comprises the above-mentioned positive electrode active material.

[0149] As mentioned above, the positive electrode active materials, adhesives, conductive materials and solvents are not subject to any particular restrictions as long as they can be used on the positive electrode current collector of the secondary battery.

[0150] Specifically, the aforementioned lithium secondary battery may include a positive electrode, a negative electrode disposed facing the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but is not particularly limited as long as it can be used as a secondary battery.

[0151] The following describes in detail the positive electrode active material of the embodiments of the present invention.

[0152] Examples 1 to 5

[0153] Preparation of precursors

[0154] Spherical Ni was formed using a co-precipitation method. x Co y Mn z(OH) precursor. In a 90L reactor, 25% by weight of NaOH and 28% by weight of NH4OH were added to a 2.5M aqueous solution of a complex transition metal sulfate, consisting of NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O with an adjusted Ni:Co:Mn molar ratio. The pH in the reactor was maintained at 9.0–12.0, and the temperature was maintained at 45°C–50°C. Inert gas N2 was introduced into the reactor to prevent oxidation of the prepared precursor. After stirring during synthesis, the precursor was washed and dehydrated using a filter press (F / P). Finally, the dehydrated product was dried at 120°C for 2 days and then sieved through a 75μm (200 mesh) sieve to obtain 4µm Ni. x Co y Mn z (OH) precursor.

[0155] First heat treatment and cooling

[0156] The above precursors are kept in a box furnace under an O2 or air atmosphere (50 L / min) and heated at a rate of 2°C per minute to maintain a temperature of 300°C to 1000°C for 1 hour to 10 hours, followed by furnace cooling.

[0157] Wet coating (the case where the first heat treatment and cooling described above are performed).

[0158] The precursor was wet-coated using a co-precipitation method. An aqueous solution of a composite transition metal sulfate, containing distilled water mixed with an adjusted molar ratio of CoSO4·7H2O, NiSO4·6H2O, or MnSO4·H2O, 25% by weight of NaOH, and 28% by weight of NH4OH, was added to a reactor containing the stirred precursor. The coating amount of the transition metal was 1 to 10 mol% relative to the total molar amounts of nickel, cobalt, and manganese. The pH in the reactor was maintained at 9.0 to 12.0. After the synthesis and stirring were completed, the product was washed and dehydrated using a pressure vessel. Finally, the dehydrated product was dried at 150°C for 14 hours to obtain a precursor with a concentration gradient.

[0159] Second heat treatment and cooling

[0160] After adjusting the Li / M ratio, weigh LiOH or Li2CO3 and mix it with the above precursor using a mixer (manual mixer, MM). Maintain the mixture in a box furnace under an O2 or air (50 L / min) atmosphere, increasing the temperature by 2°C per minute to 800°C to 1000°C for 7 to 12 hours, then cool the furnace.

[0161] Wet coating (the case where the second heat treatment and cooling described above are performed).

[0162] The aforementioned lithium composite oxide was wet-coated using a co-precipitation method. An aqueous solution of a composite transition metal sulfate, containing distilled water mixed with an adjusted molar ratio of CoSO4·7H2O, NiSO4·6H2O, or MnSO4·H2O, 25% by weight of NaOH, and 28% by weight of NH4OH, was added to a reactor containing stirred particles. The coating amount of the aforementioned transition metals was 1 to 10 mol% relative to the total molar amounts of nickel, cobalt, and manganese. The pH in the reactor was maintained at 9.0 to 12.0. After the synthesis and stirring were completed, the mixture was washed and dehydrated using a filter press. Finally, the dehydrated product was dried at 150°C for 14 hours to obtain a lithium composite oxide with a concentration gradient.

[0163] Third heat treatment and cooling

[0164] After adjusting the Li / M ratio and weighing LiOH or Li2CO3, mix it with the above coating material using a mixer (manual mixer, MM). Maintain the mixture in a box furnace under an O2 or air (50 L / min) atmosphere, increasing the temperature by 4.4°C per minute to a temperature between 300°C and 1000°C for 7 to 12 hours, then cool the furnace.

[0165] Comparative Examples 1 to 2

[0166] Except for the step of wet coating with transition metals in the preparation steps of Examples 1 to 5, the positive electrode active material was prepared in the same manner as in Examples 1 to 5.

[0167] Table 1 below relates to the preparation methods of Examples 1 to 5 and Comparative Examples 1 to 2.

[0168] Table 1

[0169]

[0170] Preparation example: Preparation of lithium secondary batteries

[0171] A positive electrode slurry was prepared by dispersing 90% by weight of the positive electrode active material of the above-described examples and comparative examples, 5.5% by weight of carbon black, and 4.5% by weight of polyvinylidene fluoride (PVDF) binder in 30g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was then coated onto a 15μm thick aluminum (Al) film serving as the positive electrode current collector and dried. Finally, a positive electrode was prepared by roll pressing.

[0172] In contrast to the above positive electrode, lithium metal was used as the counter electrode, and 1.15M LiPF6 in EC / DMC / EMC = 2 / 4 / 4 (vol.%) was used as the electrolyte.

[0173] A battery assembly is formed by inserting a separation membrane made of porous polyethylene (PE) film between the positive and negative electrodes, and the electrolyte is injected to prepare a lithium secondary battery (button cell).

[0174] Experimental Example 1

[0175] Table 2 below describes the characteristics of the lithium secondary batteries of the above-described embodiments and comparative examples.

[0176] Table 2

[0177]

[0178] It can be done Figures 1 to 3 The EP-EDX analysis results confirmed the metal concentration gradient of the positive electrode active material in the embodiment.

[0179] Furthermore, in Example 5, where cobalt is not included in the positive electrode active material and nickel is used for wet coating, it can be confirmed that a similar concentration gradient is formed as in the case of wet coating using cobalt.

[0180] It can be done Figures 4 to 7 The results of transmission electron microscopy-dispersive spectroscopy analysis confirmed the metal concentration gradient in the shell of the primary particles of the positive electrode active material in the embodiment.

[0181] It can be done Figure 8 The results of transmission electron microscopy-dispersive spectroscopy analysis confirmed the metal concentration gradient in the shell of the primary particles of the positive electrode active material in Example 5.

[0182] Figure 9 The results of scanning electron microscopy analysis are for comparative examples and embodiments.

[0183] Reference Figure 10 As shown in Table 2 above, it can be confirmed that the charge / discharge capacity and efficiency of the embodiments are increased compared to the comparative examples. This is due to the increased surface mobility caused by the concentration gradient of the shell, which increases the lithium mobility on the surface and reduces the irreversible reaction of Li2MnO3 on the surface, thereby increasing efficiency.

[0184] Reference Figures 11 to 12 As shown in Table 2 above, the rate performance of the embodiments is improved compared to the comparative examples. This is due to the increased surface motion caused by the concentration gradient of the shell.

[0185] Reference Figures 13 to 14As shown in Table 2 above, the lifetime characteristics of the embodiments are improved compared to the comparative examples. This is because the problems of lifetime degradation and voltage decay caused by phase transition during cycling of lithium excess layered oxides have been solved.

[0186] Reference Figures 15 to 16 As shown in Table 2 above, the voltage decay of the embodiment is suppressed compared to the comparative example. This is due to the improved motion and structural stability of the particle surface.

[0187] Furthermore, referring to Figures 10 to 16 As shown in Table 2 above, in Example 5, where cobalt is not included in the positive electrode active material and nickel is used for wet coating, the performance of the lithium secondary battery is also significantly improved.

Claims

1. A positive electrode active material for secondary batteries, characterized in that, The lithium complex oxide comprises a lithium excess oxide with a layered structure represented by the following chemical formula 1. The aforementioned lithium composite oxide comprises secondary particles, each secondary particle comprising one or more primary particles, and each primary particle comprising one or more grains. A shell comprising a core and at least a portion of the surface of the core, selected from one or more of the aforementioned secondary particles, primary particles, and grains. When the molar number of one or more elements selected from nickel, cobalt, and manganese is equal to the total molar number of M1 and M2 in the following chemical formula 1, the NCM / M of the shell and the core of the aforementioned secondary particle are different. The primary particle includes a nucleus and a shell. The shell of the primary particle contains a concentration gradient of nickel that decreases from the surface of the primary particle towards its center; and The shell of the primary particle contains a concentration gradient of manganese that increases from the surface of the primary particle towards its center. Chemical formula 1: rLi₂M₁O₃•(1-r)Li a M2O2, In the above chemical formula 1, 0 < r < 1, 0 < a ≤ 1, M1 contains one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi, and M2 contains one or more of Mo, Nb, Fe, Cr, V, Co, Cu, Zn, Sn, Mg, Ni, Ru, Al, Ti, Zr, B, Mn, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi.

2. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The shell of the aforementioned secondary particles contains a concentration gradient portion in which the concentrations of one or more elements selected from nickel, cobalt, and manganese are gradient.

3. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The shell and nucleus of the aforementioned primary particle have different NCM / M ratios.

4. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The shell of the aforementioned primary particle contains a concentration gradient of cobalt.

5. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The NCM / M ratios of the shell and core of the aforementioned grains are different.

6. The positive electrode active material for secondary batteries according to claim 5, characterized in that, The shell of the aforementioned grain contains a concentration gradient portion in which the concentrations of one or more elements selected from nickel, cobalt, and manganese are gradient.

7. The positive electrode active material for secondary batteries according to claim 1, characterized in that, When the number of moles of nickel relative to the total number of moles of M1 and M2 is Ni / M, the Ni / M of the shell selected from the above-mentioned secondary particles and grains is higher than that of the above-mentioned core.

8. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The shell of the aforementioned secondary particle contains a concentration gradient of nickel that decreases from the surface of the secondary particle toward the center.

9. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The shell of the aforementioned grain contains a concentration gradient of nickel that decreases from the surface of the grain toward the center.

10. The positive electrode active material for secondary batteries according to claim 1, characterized in that, When the number of moles of cobalt relative to the total number of moles of M1 and M2 is Co / M, the Co / M of the shell selected from the above-mentioned secondary particles, primary particles and grains is higher than that of the above-mentioned core.

11. The positive electrode active material for secondary batteries according to claim 1, characterized in that, The above-mentioned positive electrode active material does not contain cobalt.

12. The positive electrode active material for secondary batteries according to claim 1, characterized in that, When the number of moles of manganese relative to the total number of moles of M1 and M2 is Mn / M, the Mn / M of the shell selected from the above-mentioned secondary particles and grains is lower than that of the above-mentioned nucleus.

13. A secondary battery comprising the positive electrode active material as described in claim 1.

Citation Information

Patent Citations

  • Phase structure proportionally and gradiently changed lithium-enriched layered oxide material and preparation method thereof

    CN107785551A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and nonaqueous electrolyte secondary battery using same

    WO2014103211A1